Training Workshop on Conducting Workplace-Based Assessment (WPBA) Using Mini-Clinical Evaluation Exercise (Mini-CEX) Tool - Piryani, Rano Mal; Piryani, Suneel; Soomro, Abdul Ghani (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Mini-Clinical Evaluation Exercise (mini-CEX) is one of the valid, reliable, feasible and effective tools used for workplace-based assessment (WPBA). Faculty development is essential to train the assessors for successful implementation. Bilwal Medical College, a constituent college of Liaquat University of Medical and Health Sciences, Jamshoro Sindh Pakistan organized a one-day Training Workshop (TW) on “Conducting WPBA using mini-CEX tool” for clinical faculty members. MATERIAL AND METHODS The objectives of this descriptive cross-sectional study were to 1) report brief description of the TW and process of group-work practice session; 2) assess feedback of the participants at New World Kirkpatrick’s Model (NWKM) level I and II and 3) assess the cognition of participants about miniCEX using pretest-posttest. Feedback of the participants was taken on the valid questionnaire. Pretest and posttest were done utilizing the same format. Narrative description of the proceedings and process documented. Data of the feedback, pretest and posttest was analyzed with SPSS for central tendency and paired t-test was used for comparison. RESULTS Description of TW is documented in methods section of this article. Rating of the participants for attributes (usefulness, content, relevance, facilitation and overall) of TW and practice session on scale 1-10 (1=poor; 10=excellent) were remarkable. Signiﬁcant enhancement (p<0.001) in the level of knowledge and understanding was perceived by the participants regarding the performance-based assessment (PBA), WPBA and utility of mini-CEX as a tool for assessment. The participants perceived signiﬁcant (p<0.001) positive change in the level of conﬁdence for conducting WPBA utilizing the miniCEX tool. The cognition of the participants was signiﬁcantly (p<0.003) improved after participation in the TW revealed in pretest-posttest analysis. CONCLUSION Based on the ﬁndings of results, this TW was successful in educating medical faculty members about the utility of training for conducting WPBA, speciﬁcally with miniCEX tool.